Differential Scavenging Among Pig, Rabbit, and Human Subjects - Steadman, Dawnie Wolfe; Dautartas, Angela; Kenyhercz, Michael W.; Jantz, Lee M.; Mundorff, Amy; Vidoli, Giovanna M. (Journal of forensic sciences, 2018)
Different animal species have been used as proxies for human remains in decomposition studies for decades, although few studies have sought to validate their use in research aimed at estimating the postmortem interval. This study examines 45 pig, rabbit, and human subjects placed in three seasonal trials at the Anthropology Research Facility. In an earlier paper, we found that overall decomposition trends did vary between species that could be due to differential insect and scavenger behavior. This study specifically examines if scavenger behavior differs by carrion species. Daily photographs, game camera photographs, written observations, and Total Body Score (TBS) documented scavenging and decomposition changes. Results show that raccoons were the most commonly observed vertebrate scavenger, that scavenging was most extensive in winter, and that certain human subjects were preferred over other humans and all non‐human subjects. Finally, scavenging activity greatly reduces the accuracy of postmortem interval estimates based on TBS.